Workplace Assertiveness of Filipino Hospital Staff Nurses: A Cross-sectional Study - Oducado, Ryan Michael F.; Montaño, Hilda Clavel (Department of Nursing, Faculty of Medicine, Diponegoro University, 2021)
Background: Several studies have demonstrated the significance of assertiveness in the nursing profession. However, there is a lacuna in the literature regarding the level of workplace assertiveness of Filipino nurses.Purpose: This study determined the workplace assertiveness towards nursing colleagues, nursing management personnel, medical doctors, and other members of the health team among hospital staff nurses.Methods: The data in this cross-sectional study were collected from randomly selected staff nurses (n=223) involving two tertiary hospitals in the Philippines using the Workplace Assertive Behavior Questionnaire. Descriptive statistics and tests for differences were used to analyze the data.Results: Results showed that staff nurses had moderate workplace assertiveness. They were less assertive towards the nursing management personnel, and were less likely to provide constructive criticisms and say no to requests. Assertiveness significantly varied based on employment status (p=.001), age (p=.046), years of nursing work experience (p=.037), and years in the present organization (p=.022). A sense of responsibility to patients was the main facilitator while reprimand and fear of repercussions from the nursing management personnel were the major barriers to assertive behaviors.Conclusion: Personal and work environmental factors can inhibit or support assertiveness. This study highlighted some gaps in Filipino staff nurses’ assertiveness at work. Nursing management plays a pivotal role in nurses’ assertiveness. Efforts should be made to address the barriers and improve the assertiveness of staff nurses.